In Vitro Tracing of Cytotoxic Compounds in Jarak Cina Stem Bark (Jatropha Multifida Linn.) - Sista Werdyani; Annisa Fitria; Sari Rakhmawati (EKSAKTA: Journal of Sciences and Data Analysis, 2020)
Cancer remains one of the diseases with increasing number of sufferers, but research on compounds that act as anti-cancer is also ongoing. Terpenoids have been known as a compound that can inhibit the proliferation of cancer cells. One of the medical plants that produce terpenoids is Jarak cina (Jatropha multifida Linn.). Therefore, the possibility of Jarak cina (Jatropha multifida Linn.) to have an cytotoxic activity on cancer cell proliferation is reasonably high. This study was conducted to determine the cytotoxic activity of Jarak cina (Jatropha multifida Linn.) bark extracts against cancer cell MCF-7. Jarak cina bark was extracted using the multilevel soxhlet extraction method with n-hexane, ethyl acetate, and ethanol as the solvents. All the three extracts were then tested against MCF-7 cancer cells using MTT (3-(4,5-dimethylthiazol-2-yl) - 2,5-diphenyltetrazolium bromide) method. Data analysis was performed for IC50 (ppm) parameter. The results showed that the IC50 of n-hexane extract was 313.21 ppm, while the ethyl acetate extract reached 258.38 ppm of IC50, and the IC50 of ethanol extract was 418.51 ppm. The highest potential of cytotoxicity was found in the ethyl acetate extract, so further testing would be required to optimize the proliferation inhibitory activity.